Restructuring of regional long-term planning principles: adaptation or strategic choice - Yushkova, Nataliya (Technology audit and production reserves, 2014)
System of creating long-term plans of regional development, currently in force in Russia, with singling out the subsystems of socioeconomic planning and territorial planning and the levels in the current context, defined by the imperatives of sustainable and innovative development in it is investigated in the paper. Increasing the role of institutional factors of the development of regions requires their stipulation in complex of conceptual and legislative planning provisions, ensuring improved living standards. In order to solve the complex of problems, associated with the underestimation of regional planning, with the inconsistency of plans with conceptual development directives, with the disagreement of socioeconomic and territorial-spatial planning components, with an incomplete exploration of the real prerequisites in the regions for the implementation of innovative initiatives. The consistency of the spatial approach to regional planning, expressed in the dominant of transformational function, synchronization configuration and RES parameters with modern development imperatives was proved. Transition to the adaptive-spatial model of regional planning, ensuring completeness of accounting internal and external development factors of RES was justified. New elements of regional planning, determining the content of the planned activities and the specifics of the subjects of the regional economy were found. It was shown that innovation infrastructure defines a new design of socioeconomic space of the region, which requires recognition of its elements as special objects of regional policy. The proposed modeling of long-term planning, based on a synthesis of its socioeconomic and territorial components, provides the best adaptation of plans to the innovation development imperatives, taking into account the real possibilities of a particular region. Due to the unity of planning principles, the consistency of regional development decisions, developed at the federal and regional levels of public authority is reached, the system of regional administration is optimized, efficiency of the modernization processes in the regions is increased, disparities in living standards are reduced through rational and integrated use of resources.